Composition and species diversity of different agroforestry systems in Gondia district of Maharashtra - Kokode, Ashwini V; Taide, Y.B.; Lodh, Uday Kumar; Yadav, Dinesh (Indian Journal of Agroforestry, 2022)
The study was undertaken to assess the composition and species diversity ofdifferent agroforestry practices followed by the farmers in the Gondia district of Maharashtraduring 2018 – 2019, using the exploratory design of social research. Ten farmers each from 8villages of Arjuni Morgaon and Deori tehsil were selected for the study. Vegetation analysis wasdone through quadrate methods with a 0.1 percent sample area. The investigation revealed that thefarmers were practicing twelve different agroforestry systems in their field such as Bundplantation, Boundary plantation, Agrisilviculture, Hortisilviculture, Agrisilvipostoral,Agrihortisilviculture, Plantation along irrigation canal, Kitchen garden, Plantation near watersource, Block plantation, Scattered plantation and Avenue plantation and this classification oftwelve agroforestry systems in gondia district was followed by ( respondents in gondia district) Allthrough this study is based on data generated through survey and prepare data and participatoryRural Appraisal (PRA) efforts have been made to collect to secondary data from the village'srecords and meeting with respondents of villages. The vegetation analysis of agroforestry systemsfor Importannce Value Index (IVI) of 28 trees were recorded grown in different agroforestry systemin the study area. The IVI values ranged from 77.54 to 1.73. The lowest value (1.73) was recordedfor the Semecarpus anacardiu, while the highest value of IVI (77.54) was recorded for the Tectonagrandis, followed by Azadirachta indica (35.65), Butea monosperma (18.63), Leucaenaleucocephala (11.67) and Zizyphus mauritiana (10.55). The distribution pattern of species in thestudy area showed the maximum (2.42) and the minimum (0.048) value. The IVI results show thatthe tree species with high importance values and variation in ecologically dominant in studiedarea. Hence, the IVI has helped in understanding the ecological significance of the species in thetropicaldryclimaticzoneofGondiadistrict